(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2019)
In this article, I discuss whether the theory of justice as fairness famously proposed by John Rawls can justify the implementation of global principles of socio-economic justice, contrary to what Rawls himself maintains. In particular, I dwell on the concept of the basic structure of society, which Rawls defines as “the primary subject of justice” and considers as a prerogative of domestic societies. In the first part, I briefly present Rawls’s theory of socio-economic justice and his account of justice be- tween peoples. I then proceed with the analysis of the cosmopolitan counter-arguments that have been levelled against Rawls’s dualism between domestic and international justice, which mainly revolve around the outlining of a global basic structure as a consequence of globalisation. Between these two opposing poles, I also discuss the intermediate stance taken by those authors who maintain that the empirical dispute between a domestic and a global basic structure is misleading, because the pressing question is whether the unfair practices and norms that characterise the global economy demand the existence of a global basic structure, regardless of the fact that it already exists or not. Lastly, I collect some points, both theoretical and empirical, that have emerged from the analysis and I argue that the theoretical requirement of a global basic structure can have practical implications even if its existence is contradicted in empirical terms.